Adventitious changes in long-range gene expression caused by polymorphic structural variation and promoter competition. - Lower, K; Hughes, J; De Gobbi, M; Henderson, S; Viprakasit, V; Fisher, C; Goriely, A; Ayyub, H; Sloane-Stanley, J; Vernimmen, D; Langford, C; Garrick, D; et al. (2009)
It is well established that all of the cis-acting sequences required for fully regulated human alpha-globin expression are contained within a region of approximately 120 kb of conserved synteny. Here, we show that activation of this cluster in erythroid cells dramatically affects expression of apparently unrelated and noncontiguous genes in the 500 kb surrounding this domain, including a gene (NME4) located 300 kb from the alpha-globin cluster. Changes in NME4 expression are mediated by physical cis-interactions between this gene and the alpha-globin regulatory elements. Polymorphic structural variation within the globin cluster, altering the number of alpha-globin genes, affects the pattern of NME4 expression by altering the competition for the shared alpha-globin regulatory elements. These findings challenge the concept that the genome is organized into discrete, insulated regulatory domains. In addition, this work has important implications for our understanding of genome evolution, the interpretation of genome-wide expression, expression-quantitative trait loci, and copy number variant analyses.